2011
DOI: 10.2169/internalmedicine.50.4753
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Gene Expression of Adiponectin, Tumor Necrosis Factor-.ALPHA. and Leptin in Metabolic Syndrome Patients with Coronary Artery Disease

Abstract: Objective Metabolic syndrome (MS) is associated with an increased risk of coronary artery disease (CAD) and type 2 diabetes mellitus (DM). In MS, adipose tissue has been shown to function as a paracrine and an endocrine organ secreting various adipocytokines. In the current study, adiponectin, tumor necrosis factor-α (TNF-α) and leptin gene expressions in the epicardial adipose tissue (EAT), paracardial adipose tissue (PAT) and subcutaneous adipose tissue (SAT) were investigated in MS patients with CAD and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
2
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 33 publications
3
36
2
7
Order By: Relevance
“…Our data are also consistent with some but not all studies that have reported mRNA/gene expression profiles in SAT in subjects with MetS [36, 37]. Specifically, Gormez et al reported increased mRNA levels of TNF- α and leptin but not adiponectin in SAT from subjects with MetS versus controls [36], whereas our data showed only increased amounts of SAT-secreted and circulating leptin concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are also consistent with some but not all studies that have reported mRNA/gene expression profiles in SAT in subjects with MetS [36, 37]. Specifically, Gormez et al reported increased mRNA levels of TNF- α and leptin but not adiponectin in SAT from subjects with MetS versus controls [36], whereas our data showed only increased amounts of SAT-secreted and circulating leptin concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…With the newly established evidence that leptin has a protective role against hypoxia (4, 5), we deem that the lack of difference in the serum leptin between our 2 groups of OSA patients, with and without MS could be conceivably due to the lack of difference in the degree of hypoxia between these groups. If our assumption is correct, then in the study by Gormez et al (1), the patients with MS and CAD may have been more hypoxic than those without MS and therefore their increased leptin expression might have been due to the degree of hypoxia rather than MS itself.…”
mentioning
confidence: 84%
“…To the Editor We read with great interest the article by Gormez et al (1) dealing with the relationship between leptin and metabolic syndrome (MS) in patients with coronary artery disease (CAD). Following their interest, we attempted to confirm a similar positive relationship between leptin and MS in obstructive sleep apnea (OSA) patients.…”
mentioning
confidence: 99%
“…Sacks et al (121) has shown that pioglitazone treatment of T2DM patients with CAD is associated with a reduction of proinflammatory and anti-inflammatory genes (IL-1␤, IL-1Ra, and IL-10) in EAT and that a selective increase in PPAR␥ is observed in SAT. Although EAT has been reported to be a source of both proinflammatory and anti-inflammatory markers, mounting evidence suggests that local secretion of proinflammatory cytokines from EAT are more predominant and could downregulate the protective and anti-inflammatory cytokines along with adiponectin and adrenomedullin in severe CAD (4,22,42,63,99,126).…”
Section: Eat Adipocytokines and Their Role In Atherosclerosismentioning
confidence: 99%